Phosphatidylinositol-4, 5-Biphosphate (PI(4, 5)P2) Is Required for Rapid Endocytosis in Chromaffin Cells. (10th September 2020) - Azizi, Fouad
Abstract : Objective . Phosphoinositides play a regulatory role in clathrin-mediated endocytosis. However, their involvement in clathrin-independent endocytosis termed rapid endocytosis (RE), which is the mode of vesicle recycling during neurotransmitter release by transient fusion (known as kiss-and-run), has not been investigated. Here, we used patch-clamp recording of whole-cell membrane capacitance in adrenal chromaffin cells (ACC) to monitor changes of RE kinetics in response to pharmacological alteration of phosphatidylinositol-4, 5-biphosphate (PI(4, 5)P2 ) level by phenylarsine oxide (PAO) or antibody against phosphatidylinositol 4-kinase (AbPI4K ). Results . We found that PAO and AbPI4K significantly abrogated RE kinetics. Infusion of PI(4, 5)P2 through the patch pipette potentiated RE kinetics and reversed PAO- and AbPI4K -induced blockade of RE. Similarly, the application of the bifunctional thiol dithiothreitol (DTT) to PAO-treated cells completely prevented the inhibitory effect of PAO on RE. These findings indicate that PI(4, 5)P2 is implicated in the signaling (mechanistic) process of RE in ACC.